6+6x you multiply 3 and 2 but you can’t add the 6x because the first 6 doesn’t have an x so it would stay as 6+6x
We have such equation
5x-3y=12 /-5x (subtract 5x both sides)
5x-5x-3y=12-5x
-3y=-5x+12 /:3 divide both sides by 3
-y=
![\frac{-5x+12}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5x%2B12%7D%7B3%7D%20)
/*(-1) multiply both sides by -1
y=-
![\frac{-5x+12}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5x%2B12%7D%7B3%7D%20)
y=
![\frac{5x-12}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5x-12%7D%7B3%7D%20)
- its the answer
You add 7 to 19, so 26 and then divide it by 4.
X= 6.5
The quadratic formula is ![\frac{-b+-\sqrt[2]{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B-%5Csqrt%5B2%5D%7Bb%5E2-4ac%7D%7D%7B2a%7D)
and in the equation ax^2+bx+c=0
so now all you have to do is substitute the numbers into the quadratic formula
<h2><u>EQUATION</u></h2><h3>Exercise</h3>
2(3 + 3y) + y = 11
First, apply the distributive property:
2(3 + 3y) + y = 11
6 + 6y + y = 11
6 + 7y = 11
Substract 6 from both sides:
6 - 6 + 7y = 11 - 6
7y = 5
Divide both sides by 7:
![\dfrac{7y}{7} = \dfrac{5}{7}](https://tex.z-dn.net/?f=%5Cdfrac%7B7y%7D%7B7%7D%20%3D%20%5Cdfrac%7B5%7D%7B7%7D)
![\boxed{y = \dfrac{5}{7}}](https://tex.z-dn.net/?f=%5Cboxed%7By%20%3D%20%5Cdfrac%7B5%7D%7B7%7D%7D)
<h3><u>Answer</u>. The value of y = 5/7.</h3>